2011
DOI: 10.1097/aln.0b013e31820c2b57
|View full text |Cite
|
Sign up to set email alerts
|

Bispectral Index Monitoring, Duration of Bispectral Index Below 45, Patient Risk Factors, and Intermediate-term Mortality after Noncardiac Surgery in the B-Unaware Trial

Abstract: Background: Postoperative mortality has been associated with cumulative anesthetic duration below an arbitrary processed electroencephalographic threshold (bispectral index [BIS] Ͻ45). This substudy of the B-Unaware Trial tested whether cumulative duration of BIS values lower than 45, cumulative anesthetic dose, comorbidities, or intraoperative events were independently associated with postoperative mortality. Methods: The authors studied 1,473 patients (mean Ϯ SD age, 57.9 Ϯ 14.4 yr; 749 men) who underwent no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(74 citation statements)
references
References 30 publications
5
66
1
2
Order By: Relevance
“…Estudiamos esta asociación dado que el descenso brusco e inexplicable del BIS se ha relacionado con hipoperfusión cerebral [28][29][30][31][32][33][34] , sugiriéndose que este monitor ayudaría a detectar una hipoperfusión cerebral aguda en pacientes de alto riesgo 27,[31][32][33][34] . A pesar de estos reportes, no se ha observado asociación entre BIS y morbi-mortalidad postoperatoria 35,43,59,60 , por lo que no se ha recomendado su uso rutinario en una población no seleccionada de pacientes 27,[60][61][62] . La puntuación del RAVLT basal fue la única diferencia signifi cativa entre los grupos estudiados (Tabla 2).…”
Section: Discussionunclassified
“…Estudiamos esta asociación dado que el descenso brusco e inexplicable del BIS se ha relacionado con hipoperfusión cerebral [28][29][30][31][32][33][34] , sugiriéndose que este monitor ayudaría a detectar una hipoperfusión cerebral aguda en pacientes de alto riesgo 27,[31][32][33][34] . A pesar de estos reportes, no se ha observado asociación entre BIS y morbi-mortalidad postoperatoria 35,43,59,60 , por lo que no se ha recomendado su uso rutinario en una población no seleccionada de pacientes 27,[60][61][62] . La puntuación del RAVLT basal fue la única diferencia signifi cativa entre los grupos estudiados (Tabla 2).…”
Section: Discussionunclassified
“…122 Congruent with those findings, Kertai and coauthors concluded that results from the B-Unaware trial ''do not support the hypothesis that limiting depth of anesthesia either by titration to a specific BIS threshold or by limiting end-tidal volatile agent concentrations will decrease postoperative mortality.'' 123 If the association between POCD and mortality is valid and causal, 87 the Kertai conclusion 123 would also imply that maintaining a high BIS does not reduce POCD. In an editorial accompanying that article, Kalkman and Peelen reminded readers that ''.…”
Section: A Study By Schubert's Group Looked At Lighter Anesthesia (Bimentioning
confidence: 99%
“…Patients were maintained on infusions of propofol ranging from 25 to 200 mcg/kg/min titrated to a BIS target of 50 ± 5 and an infusion of remifentanil ranging from 30 to 100 ng/kg/min with no further use of muscle relaxants. Controlled ventilation with an endotracheal tube (ET) was maintained with an ETCO 2 = 33 ± 3 and respiratory rate (RR) [8][9][10][11][12].…”
Section: Methodsmentioning
confidence: 99%